PENINGKATAN KESEJAHTERAAN PEREMPUAN DENGAN PEMANFAATAN TEKNOLOGI PEMBUAT JAMU CAIR TRADISIONAL - Sanosra, Abadi; Kosjoko, Kosjoko; Umarie, Iskandar; Gunasti, Amri (Jurnal Abdi Insani, 2025)
Adolescence is a period of rapid growth and development, physically,psychologically, and intellectually. Teenagers still have limited knowledge abouthealthy living behaviors and the risks of negative behaviors. Improvement ofAdolescent Health Knowledge and Character Through the SMART YouthProgram, students will receive training on mental health, stress management,responsible decision-making, and strengthening adolescent character. The aimof this community service is to enhance teenagers' knowledge and awarenessabout the importance of healthy living behaviors and stress management andinstill SMART character values (healthy, independent, active, religious, andresponsible) in teenagers' daily lives. The activity methods were carried outthrough the delivery of materials, educational films, training, integrationpractices, and question-and-answer sessions. Topics include reproductivehealth, stress management, life skills, physical and social activity, ethics andreligious values in adolescent life, discipline, and integrity in daily life. Thisactivity was conducted on Wednesday, February 28, 2025, with 30 participants.The success of the activity was measured using a questionnaire. The resultsshow an increase in knowledge from the category of sufficient knowledge togood, with teenagers increasingly understanding the importance of maintainingphysical and mental health, being able to act independently, being active inpositive activities, upholding religious values, and being responsible in everyaction. Conclusion: expanding students' knowledge and skills in facingadolescent challenges, as well as supporting the formation of a healthy, happy,and responsible adolescent character. Suggestion: It is expected to continueand integrate SMART values into learning activities and counseling guidancesustainably as part of student character development.